Morphological and genetic analysis of Milnesium cf. granulatum (Tardigrada: Milnesiidae) from Northeastern North America‡ - Jackson, Kathy Jo A.; Meyer, Harry A. (Zootaxa, 2019)
Specimens of a limnoterrestrial tardigrade collected from moss in New Hampshire, USA and Newfoundland, Canada were identified as belonging to the genus Milnesium. Morphometric data and genetic analysis of the COI gene demonstrated that animals collected from these sites represent the same species. Specimens most closely resemble Milnesium granulatum, a South American species that has been reported also from Great Smoky Mountains National Park (GSMNP), USA. New Hampshire and Newfoundland animals have the same adult claw configuration and cuticular granulation pattern as M. granulatum. Theira* (i.e., normalized to correct for allometric effects) pt values differ from GSMNP M. granulatum in having a more posterior stylet support insertion point. However, all their morphometric values overlap in range with GSMNP specimens. Unlike some other species in the genus, the claw configuration of New Hampshire Milnesium cf. granulatum shows no ontogenetic change in claw configuration. A short (269 bp on average) fragment of the internal transcribed spacer region 2 (ITS-2) was sequenced for 20 New Hampshire adults and from siblings hatched in the laboratory from 8 egg clutches. Genetic diversity among New Hampshire adults was 0.0–3.7%. Multiple haplotypes were found between siblings in a single clutch.